Waist circumference of adolescents in Peru - Pajuelo Ramírez, Jaime (2016)
Introduction. Waist circumference is an important anthropometric measure in the study of obesity, but there is no reference from a national population. Objective. To present a smoothed reference percentile and to show some characteristics of variables studied. Design. Descriptive, observational, cross-sectional study. Participants. Teenagers. Interventions. Waist circumference was measured in 8 236 adolescents aged 14 to 19 years old. Main outcome measures. Averages, standard deviation and prevalence of cardiovascular risk. Results. A national reference of waist circumference values is presented and the value corresponding to the 90 percentile is taken as cutoff level to identify adolescents with cardiovascular risk. Of the population studied, 12% were at risk. Those presenting higher risk were the male adolescents (12.1%), those living in urban areas (15.9%), in the Southern Coast (27.1%), in Metropolitan Lima (19.9%), and in cities below 1 000 m (15.4%); obese adolescents (94.8%) and those considered non-poor (14.7%). With the exception of gender, other variables presented statistically significant association with waist circumference. Conclusions. The cardiovascular risk appeared already present at an early age, making it necessary to take appropriate management measures.